Projeto e implementação de lâmpadas para iluminação de interiores empregando diodos emissores de luz(LEDS) - Pinto, Rafael Adaime (2008)
This work presents an efficient lighting system using high intensity light emitting diodes (LEDs). The goal is to develop a compact and low cost electronic circuit to drive and control the current of LEDs disposed in a single enclosure. The proposal aims energy saving, high luminous efficacy and high useful life when replacing traditional lighting systems, as dichroic, incandescent or compact fluorescent lamps by LEDs without any change in electrical system installation. Furthermore, an emergency lighting system integrated into the lamp is proposed, allowing the use of the same equipment in the daily activities, supplied by mains, and under a possible break in the electrical network. To supply the LEDs through the mains with universal input voltage and charge the battery, a Buck converter was employed. To supply the LEDs with a continuous current through the battery, a Boost converter was used. The converters operate at high frequency and control the current through the LEDs independently. The battery can be composed of three rechargeable Ni-MH batteries (1,2 V) or a Li-ion battery (3,6 V). The design attends the Brazilian standard and international standard for emergency lighting systems. To validate the proposed idea, the circuits were designed and implemented. The experimental results are shown with the intention to prove the satisfactory behavior of the lamps.